The impact of psychopathy on imputability. An analysis of case law and a proposal for application in Spain criminal law - Casanueva Sanz, Itziar (2021)
This work aims at analysing the repercussion that psychopathy may have on the criminal imputability and, therefore, on the criminal liability of the person who suffers it, taking as a reference the Spanish criminal legal system. Due to the existing terminological confusion in this regard, the work also refers to personality disorders, mainly antisocial personality disorder. This analysis has as its central axis the most recent case law of the Spanish Supreme Court, which is the object of this study and allows us to propose what is the most appropriate way to assess criminal imputability in these cases. Specifically, this paper debates the possibility of applying the circumstances for exonerating and mitigating the criminal penalty of articles 20.1, 21.1 and 21.7 of the Spanish Penal Code when these disorders affect, mainly, affectivity and impulse control. Since imputability is an element of the definition of the crime that requires the analysis of the individual’s psychic abilities, its study requires the contributions of the health sciences; contributions that cannot be ignored by the law. On the contrary, they must be taken into account, as far as possible. For this reason, throughout the text there are numerous references to these sciences, especially the dsm-5 and icd-10, two international classifications of mental disorders that have the endorsement of prestigious psychiatrists.